FRI0386 The validation of the scleroderma health assessment questionnaire in turkish speaking patients with systemic sclerosis. (15th June 2017) - Karadag, D Temiz; Karakas, F; Tekeoglu, S; Ozdemir, O Işik; Yazici, A; Cefle, A
Abstract : Background: The Health Assessment Questionnaire (HAQ) is one of the main instruments for assessing disability in rheumatic diseases.The Scleroderma HAQ (S-HAQ) combines the HAQ with five systemic sclerosis (SSc) related visual analogue scales for Raynaud's phenomenon (RP), digital ulcers, digestive symptoms, pulmonary symptoms, and overall disease severity. Objectives: To perform cross-cultural adaptation and validation of the S-HAQ in patients with SSc. Methods: Sixty patients who fulfilled the 2013 ACR/EULAR Classification Criteria for Systemic Sclerosis ACR criteria for SSc were were recruited.Fifty three percent of the patients fulfilled the criteria for limited systemic sclerosis (lcSSc).We evaluated test–retest reliability using the intraclass correlation coefficient (ICC); known-groups construct validity by stratifying patients according to severe organ involvement; and convergent validity using Spearman's correlation with mental and physical components of Short Form 36 version 2 (SF36v2). Results: Eighty percent of the patients were female and the median age was 56 years old.Finger tip ulcers were observed in 16 patients (26.7%) and severe organ involvements were detected as intersititial lung disease in 32 (53%) and pulmonary hypertension in 5 (8%) of the patients.HAQ Disability Index (HAQ-DI), digestive VAS, pulmonary VAS, digital ulcer VAS, Raynaud's phenomenon VAS and overall disease severity VAS demonstrated high reliability (ICCs=0.819–0.908).The HAQ-DI showed higher correlation coefficients with physical function and role physical components of physical-related scores (r=-0.537 and – 0.453, respectively); social function and role emotional components of mental-related dimensions (r= -0.470 and -0.328, respectively) in the SF-36.Two among five SSc related VAS (VAS digital ulcer and VAS overall disease severity) were highly correlated with HAQ-DI (r=0.527 and 0.481 respectively).The instruments could not discriminate between severe organ involvements and both subsets of SSc. Conclusions: The Turkish version of the S-HAQ meet the requirements of reproducibility and validity.More studies are needed to examine the capacity of these instruments to discriminate between severe involvements and disease subsets.This study forms the basis for future studies to evaluate the properties of S-HAQ in Turkish speaking SSc patients more extensively. References: R Hesselstrand et al, Psychometric properties of the Swedish version of the Scleroderma Health Assessment Questionnaire and the Cochin Hand Function Scale in patients with systemic sclerosis, Scandjrheumatol Vol. 42, Iss. 4, 2013. Disclosure of Interest: None declared